Sosialisasi Pertolongan Pertama pada Korban Tenggelam bagi Petugas Penjaga di Kolam Renang Siharang-Karang, Kota Padangsidimpuan - Febrina Angraini Simamora; Fahrizal Alwi (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
The Siharang-Karang Swimming Pool is one of the most visited pools by the people of Padangsidimpuan, especially on weekends. The large number of visitors in this swimming pool causes a very high risk of drowning victims. There are 4 pool guard officers who are on duty every day to monitor the activities in the pool, and help if there is a problem at the pool location, for example a drowning victim. Because it is necessary to carry out activities in the form of socialization of first aid to drowning victims for pool guard officers. The treatment for the drowning victim at the scene includes rescuing the victim from water, giving breath assistance, chest compressions, clearing vomit that allows obstruction of the airway, preventing heat loss and transportation of the victim to the nearest emergency facility for evaluation and monitoring. This activity provides provisions and trains pool guard officers to have good skills in providing first aid in an emergency situation of drowning victims. With this training, it is hoped that it will increase the safety rate for emergency victims because they receive proper first aid before arriving at the health service and receive further treatment.